Procedural generation of programming exercises with guides based on the student's emotion - Tiam-Lee, Thomas James Z. (Animo Repository, 2018)
We discuss an approach in procedurally generating coding exercises for programming practice without using param- eterized questions. We applied our approach in the development of a system that can adjust the complexity of the programming exercises generated based on the presence of confusion on the student. A guide for each exercise can also be presented when confusion is detected. We tested our system on university students. 62.68% and 68.57% of the students found the exercises to be fun and helpful in programming practice, respectively. In addition, we also found that adjusting complexity and providing guides based on confusion has a positive impact on the number of problems solved. This study can lay the foundation for the development of programming intelligent tutoring systems that can generate personalized learning content such as controlling the difficulty of exercises based on the proficiency of the student and presenting exercises that are engaging for the learner.